KEEFEKTIFAN Trichoderma sp. DAN Fusarium NON PATOGENIK DALAM MENGENDALIKAN PENYAKIT BUSUK PUCUK VANILI BERWAWASAN LINGKUNGAN / Effectiveness of Trichoderma sp. and non-pathogenic Fusarium to Environmentally Control Vanilla Shoot Rot Disease - Efi Taufiq; Hasim Hasim; Bonny PW Soekarno; M. Surahman (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Vanilla shoot rot disease (VSR) is one of important disease that potentially reduces Indonesia’s vanilla production. The VSR disease is prevalently developing in the nursery, but due to the extreme climate change, the disease occurrence in the garden has increased recently. A present study was aimed to assess the effectiveness of Trichoderma sp. and non-pathogenic Fusarium (NPF) in controlling the VSR disease in the garden. An experiment was conducted in a vanilla garden at KP Sukamulya, Sukabumi November 2015 - July 2016. The study consisted of five treatments that were application of Trichoderma sp. substrate (T) onto the vanilla tips, spraying the conidial suspension of FusNP (F), a combine application of Trichoderma sp. and FusNP (TF), synthetic fungicide mancozeb (M) and the control (K). The treatments were arranged in a randomized block design, replicated five times each. The variables measured were the incidence and severity of VSR diseases monthly, residue of synthetic fungicides and rainfall. The results showed that application of Trichoderma sp. sp. and NPF reduced the disease severity of VSR 3 % and 5 % respectively than the one of control. While the fungicide application was 3% lower than the control. The VSR disease progress is affected significantly by rainfall period. Keyword: vanilla shoot rot disease, Phytophthora capsici. Bioagent. AbstrakPenyakit busuk pucuk vanili (BPV) merupakan salah satu penyakit penting vanili yang berpotensi mengurangi produksi vanili di Indonesia. Penyakit BPV di Indonesia umumnya merusak pembibitan, namun akibat perubahan iklim yang ekstrim, serangan penyakit BPV pada tanaman vanili dewasa di kebun mengalami peningkatan. Penelitian dilakukan untuk mengetahui keefektifan Trichoderma sp. dan Fusarium non patogenik (FusNP) dalam mengendalikan penyakit BPV di kebun vanili. Penelitian lapangan dilakukan di KP Sukamulya, Sukabumi mulai November 2015 - Juli 2016. Pengujian residu fungisida sintetik dilakukan di Laboratorium Residu Bahan Agrokimia Balai Penelitian Lingkungan Pertanian, Laladon Bogor. Penelitian terdiri atas lima perlakuan yaitu pemberian substrat Trichoderma sp. (T), penyemprotan suspensi konidia FusNP (F), kombinasi Trichoderma sp. dan FusNP (TF), fungisida sintetik mancozeb (M) dan kontrol (K). Perlakuan disusun dalam rancangan acak kelompok (RAK), tiap perlakuan diulang sebanyak lima kali. Variabel yang diamati adalah gejala dan keparahan penyakit, curah hujan, dan residu fungisida sintetik. Data dianalisis dengan Uji Tukey pada selang kepercayaan 95%. Hasil penelitian menunjukkan bahwa Trichoderma sp. dan FusNP cukup efektif mengendalikan penyakit BPV di lapangan, setara dengan keefektifan fungisida sintetik yaitu kejadian penyakit berkisar 2 - 5%, sedangkan kontrol mencapai 32%. Perkembangan penyakit BPV dipengaruhi oleh curah hujan, semakin tinggi curah hujan semakin tinggi intensitas serangan penyakit BPV. Penggunaan fungisida sintetik secara intensif menyebabkan pencemaran lingkungan berupa residu pestisida pada daun, buah, dan tanah rizosfer vanili..Kata kunci: busuk pucuk vanili, Phytophthora. capsici, agens hayati. ABSTRACTVanilla shoot rot disease (VSR) is one of important disease that potentially reduces Indonesia’s vanilla production. The VSR disease is prevalently developing in the nursery, but due to the extreme climate change, the disease occurrence in the garden has increased recently. A present study was aimed to assess the effectiveness of Trichoderma sp. and non-pathogenic Fusarium (NPF) in controlling the VSR disease in the garden. An experiment was conducted in a vanilla garden at KP Sukamulya, Sukabumi November 2015 - July 2016. The study consisted of five treatments that were application of Trichoderma sp. substrate (T) onto the vanilla tips, spraying the conidial suspension of FusNP (F), a combine application of Trichoderma sp. and FusNP (TF), synthetic fungicide mancozeb (M) and the control (K). The treatments were arranged in a randomized block design, replicated five times each. The variables measured were the incidence and severity of VSR diseases monthly, residue of synthetic fungicides and rainfall. The results showed that application of Trichoderma sp. sp. and NPF reduced the disease severity of VSR 3 % and 5 % respectively than the one of control. While the fungicide application was 3% lower than the control. The VSR disease progress is affected significantly by rainfall period. Keyword: vanilla shoot rot disease, Phytophthora capsici. Bioagent.